Drying and Wetting of Building Materials and Components - Delgado, J.M.P.Q.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book, Drying and Wetting of Building Materials and Components, provides a collection of recent contributions in the field of drying and wetting in porous building materials. The main benefit of the book is that it discusses some of the most important topics related to the drying and wetting processes, namely, innovations and trends in drying science and technology, drying mechanism and theory, equipment, advanced modelling, complex simulation and experimentation. At the same time, these topics will be going to the encounter of a variety of scientific and engineering disciplines. The book is divided in several chapters that intend to be a resume of the current state of knowledge for benefit of professional colleagues.
Air Drying Technologies Applied to Buildings Treatment -- Moisture Transfer Kinetics in Building Materials and Components: Modeling, Experimental Data, Simulation -- Wetting and Drying Kinetics of Building Materials -- Pore Structure Parameters and Drying Rates of Building Materials -- Setting and Drying of Bio-Based Building Materials -- Modelling of Wetting and Drying Cycles in Building Structures -- A Review of Drying Theory and Modelling Approaches -- Cost Effective and Energy Efficient Control of Indoor Humidity in Buildings with Hygroscopic Building Materials and Desiccants in the HVAC System -- Risk of Condensation in Mechanically Attached Roof Systems in Cold U.S. Climate Zones.  .
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Structural materials; Building materials; Engineering Thermodynamics, Heat and Mass Transfer; Structural Materials; Building Materials